ORBIT: a New Paradigm for Genetic Engineering of Mycobacterial Chromosomes - Kenan C. Murphy (American Society for Microbiology, 2018)
ABSTRACT Two efficient recombination systems were combined to produce a versatile method for chromosomal engineering that obviates the need to prepare double-stranded DNA (dsDNA) recombination substrates. A synthetic “targeting oligonucleotide” is incorporated into the chromosome via homologous recombination mediated by the phage Che9c RecT annealase. This oligonucleotide contains a site-specific recombination site for the directional Bxb1 integrase (Int), which allows the simultaneous integration of a “payload plasmid” that contains a cognate recombination site and a selectable marker. The targeting oligonucleotide and payload plasmid are cotransformed into a RecT- and Int-expressing strain, and drug-resistant homologous recombinants are selected in a single step. A library of reusable target-independent payload plasmids is available to generate gene knockouts, promoter replacements, or C-terminal tags. This new system is called ORBIT (for “oligonucleotide-mediated recombineering followed by Bxb1 integrase targeting”) and is ideally suited for the creation of libraries consisting of large numbers of deletions, insertions, or fusions in a bacterial chromosome. We demonstrate the utility of this “drag and drop” strategy by the construction of insertions or deletions in over 100 genes in Mycobacterium tuberculosis and M. smegmatis. IMPORTANCE We sought to develop a system that could increase the usefulness of oligonucleotide-mediated recombineering of bacterial chromosomes by expanding the types of modifications generated by an oligonucleotide (i.e., insertions and deletions) and by making recombinant formation a selectable event. This paper describes such a system for use in M. smegmatis and M. tuberculosis. By incorporating a single-stranded DNA (ssDNA) version of the phage Bxb1 attP site into the oligonucleotide and coelectroporating it with a nonreplicative plasmid that carries an attB site and a drug selection marker, we show both formation of a chromosomal attP site and integration of the plasmid in a single transformation. No target-specific dsDNA substrates are required. This system will allow investigators studying mycobacterial diseases, including tuberculosis, to easily generate multiple mutants for analysis of virulence factors, identification of new drug targets, and development of new vaccines.